The Influence of Human Resource Competence in Marketing on Sales Performance of (SMEs) in Indonesia: Pengaruh Kompetensi Sumber Daya Manusia dalam Pemasaran terhadap Kinerja Penjualan (UKM) di Indonesia - M. Fadillah (Journal of State Economic Research, 2025)
This study examines the impact of human resource (HR) competencies in marketing on the sales performance of small and medium enterprises (SMEs) in Indonesia. Data were collected through a survey of 100 SMEs across various sectors and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The HR competencies assessed include product positioning, relational marketing, and channel management, which were tested against four performance indicators: sales growth, profitability, operational efficiency, and customer satisfaction. The findings indicate that HR marketing competencies exert a positive and significant influence on all performance dimensions, with the strongest effects on sales growth (β=0.621) and profitability (β=0.581), followed by operational efficiency (β=0.541) and customer satisfaction (β=0.491). These results are consistent with prior studies highlighting the role of marketing-oriented HR competencies in enhancing firm revenues. Theoretically, this study reinforces the Resource-Based View (RBV) and Dynamic Capabilities Theory within the SME context, while practically recommending investments in competency-based training and the adoption of simplified performance evaluation systems to foster sustainable SME growth.